Shortcuts to adiabaticity in a fast controlled-phase gate in superconducting quantum circuits - Li, Jia-Xin; Cárdenas-López, F. A.; Chen, Xi (Frontiers in Quantum Science and Technology, 2023)
Based on the renewed interest in the shortcut-to-adiabaticity techniques in quantum control, we propose a reverse-engineering approach to modulate the coupling between a pair of two-level systems longitudinally with a quantized single-mode resonator. This allows us to suppress the unwanted transitions in the time-evolution operator such that the system dynamics resemble a controlled-phase gate acting in the qubit subspace at the nanosecond scale. The reduced gating time mitigates the detrimental effect produced by the loss mechanisms in all the parties. Moreover, we present a possible experimental implementation based on superconducting quantum circuits. Our work further demonstrates the versatility of reverse-engineering method to enhance quantum protocols based on circuit quantum electrodynamic architecture.